Functional outcome 6 months after severe traumatic brain injury following admission to intensive care unit: A follow-up study in two neuro-center hospitals - Abdul Rashid, Nor'ain; Mohamed Ludin, Salizar; Mat Nor, Mohd Basri; Awang, Mohamed Saufi (2017)
Study Background: Traumatic brain injury (TBI) is a major medical and socioeconomic problem and is the leading cause of death in the young adult. Patients with severe TBI shows physical and functional improvement but remain with cognitive and psycho-social problem throughout recovery. Despite all these issues, the impact of TBI on long-term survivors in Malaysia is unknown. The aim of this study is to measure the functional level of ICU survivors’ with severe TBI within 6 months post injury Methods: A cohort study was employed for this study. 33 participants from Hospital Tengku Ampuan Afzan (HTAA) Kuantan, Pahang and Hospital Sultanah Nur Zahirah (HSNZ) Kuala Terengganu with severe TBI were included in this study. The functional assessment of Glasgow Outcome Scale Extended (GOSE) was measured on all samples within 6 months period. Results: The participants mean age was 31.79 ranging from 16 to 73 years old. The result of this study showed that within 3 months after discharge from the hospital, all the participants were still poorly recovered, n=33 (100.0%). Meanwhile, after 6 months being discharged from the hospital, 48.5% of the participants scored a good recovery score. In this case, the SOFA and SAPS II scores contributed significantly to the prediction (SOFA score p=0.045, SAPS II score p=0.028) of the functional outcome. Conclusion: The functional outcome of severe TBI was improved in six months post injury. The SOFA score and SAPS II score become significant markers for the functional outcome in this study. Nonetheless, there were some limitations related to this study, which is a small sample size and time constraint. From this study, the health care provider can use SOFA and SAPS II score as the predictors for the functional outcome, thus, an early care plan can be done if severe TBI patients have high SOFA or SAPS II scores.